Emergency Remote Teaching during COVID-19 Lockdown and Its Implications for Higher Education Institutions: An International Perspective - Makarova, Elena; Göbel, Kerstin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In spring 2020, the COVID-19 virus and subsequent lockdown demanded that university institutions across the globe undertake an emergency migration to online teaching. To secure the continuation of university teaching, Emergency Remote Teaching (Bozkurt and Ramesh, 2020)-prompt rethinking and adjustment among university teachers-had to be managed. On the one hand, this abrupt change is associated with a certain digital and pedagogical potential for change due to the necessary adaptation efforts. On the other hand, it also poses an extraordinary organisational and pedagogical challenge. From an empirical perspective, it is therefore crucial to ask how university teachers and universities are tackling the coronavirus situation against the backdrop of the goal to maintain high-quality teaching. Furthermore, the adjustment and well-being of students in the context of hybrid and distance learning situations must remain in focus. The aim of this Special Issue was to provide unique insights into organisational, pedagogical, and psychological challenges related to digital transition in Higher Education institutions in different countries resulting from university lockdowns during the COVID-19 pandemic. It also discusses digital and pedagogical potentials evolving through the adaptation efforts related to the situation of Emergency Remote Teaching at universities.